To lead or not to lead: The fluctuation of peer leadership in collaborative oral argumentation - Wu, Qian; Feng, Pengpeng; Gu, Mingyue Michelle (Studies in Second Language Learning and Teaching, 2025)
Working with peers in small groups is conducive to learning, and collaborative learning has been widely adopted in second language classrooms. Leadership, defined as the initiative taken to influence others in a group, plays a significant role in successful teamwork, but has not received due attention in research on collaborative peer work. To address this research gap, we conducted a case study in a university English as a foreign language classroom in China in which the participants navigated their oral argumentation tasks collaboratively. The current study offers insight into the fluctuation of peer leadership in collaborative oral argumentation based on group discussion and semi-structured interview data. The findings suggest that peer leadership is a dynamic process that fluctuates in function and individual contribution over time. The study also revealed that peer leadership is a complex process influenced by multiple factors, including intrapersonal, interpersonal, and task-related ones. In conclusion, we stress that, to optimize collaborative peer learning, teachers should strive to stimulate and nurture the emergence of leadership and provide space for its long-term development.